The role of extrachromosomal DNA in tumorigenesis and progression - Ma, Xiaoyang; Yu, Xiaolin; Wu, Chuan; Song, Lixing (Frontiers in Oncology, 2025)
In tumors, extrachromosomal DNA (ecDNA) is an important driver of oncogene expression, genomic instability, the evolution of drug resistance, and poor patient prognosis. ecDNA is present in various tumors but is rarely found in normal cells. Here, we provide a detailed review of the structure, genetics, occurrence, outcomes, and functions of ecDNA, offering further reference for research on ecDNA.